Peningkatan Mutu Pendidikan Melalui Penilaian Proses Belajar Mengajar - Nurrohman, Moh; Haryati, Titik (Faculty Of Education, 2024)
Assessment of the results of the implementation of the teaching and learning process is often ignored, and very rarely carried out. The quality of education is only measured by the success of students after participating in the teaching and learning process. This paper aims to examine efforts to improve quality through assessing the teaching and learning process. The quality of education is not only measured by the product, but starts from the input, process and output dimensions. In this case, in accordance with the dimensions of assessment of the teaching and learning process which includes input-process and output as well as continuous improvement is the essence of assessment of the teaching and learning process. The results of the study show that the teaching and learning process as an object of assessment is very appropriate to carry out, especially in efforts to improve the quality of education. Efforts to improve the quality of education are carried out based on the results of the assessment of the teaching and learning process.